1968
DOI: 10.1161/01.res.22.5.559
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pituitary, Thyroid, and Adrenal Hormones on Norepinephrine Turnover and Metabolismin the Rat Heart

Abstract: Norepinephrine turnover was estimated in the rat heart from the rate of release of tracer 3 H-norepinephrine and the depletion of endogenous norepinephrine after inhibition of synthesis. Cardiac norepinephrine turnover was markedly increased in chronically hypophysectomized rats. Thyroidectomy and adrenalectomy were also associated with increased cardiac norepinephrine turnover, whereas ovariectomy was not. Chronic treatment of hypophysectomized rats with thyroxine and ACTH restored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
2
1

Year Published

1969
1969
1997
1997

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 13 publications
4
40
2
1
Order By: Relevance
“…Noradrenaline turnover rate was shown to increase after thyroidectomy (Tu & Nash, 1975;Tedesco, Flattery & Sellers, 1977) or hypophysectomy (Landsberg & Axelrod, 1968), and an increased tonic release of the neurotransmitter may down-regulate postsynaptic receptors (Raff, 1976). This mechanism, however, cannot explain the present findings.…”
Section: Discussioncontrasting
confidence: 68%
“…Noradrenaline turnover rate was shown to increase after thyroidectomy (Tu & Nash, 1975;Tedesco, Flattery & Sellers, 1977) or hypophysectomy (Landsberg & Axelrod, 1968), and an increased tonic release of the neurotransmitter may down-regulate postsynaptic receptors (Raff, 1976). This mechanism, however, cannot explain the present findings.…”
Section: Discussioncontrasting
confidence: 68%
“…Thus the rapid decline in 3H-noradrenaline in adrenalectomized or demedullated rats, at 24 hr after its administration, indicates increased noradrenline turnover and synthesis. These results are consistent with those of Landsberg & Axelrod (1968).…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, hypothyroidism might be involved as Tahiliani & McNeil (1985) have reported depressed plasma levels of both T3 and T4 in 6-week streptozotocin-diabetic rats and hypothyroidism has been found to increase cardiac sympathetic activity whether measured by [3H]-NA turnover or, as here, by tissue NA decline following AMPT (Landsberg & Axelrod, 1968). Na', K+-ATPase activity has been reported to be depressed by hypothyroidism and increased by T3 administration (Norgaard et al, 1983).…”
Section: Discussionmentioning
confidence: 63%
“…Such a hypothesis does not, however, explain its prevention by MI or Statil unless such treatment prevented the hypothyroidism. The elevation of tissue NA in the absence of AMPT is unlikely to be due to hypothyroidism since Landsberg & Axelrod (1968) found no NA elevation in their hypothyroid rats and Ganguly et al (1987) found no effect of T3 administration on the elevated tissue NA which they observed in diabetic rats. The latter paper reported a decrease in the proportion of [3H]-NA recovered from a cardiac tissue fraction containing the storage vesicles.…”
Section: Discussionmentioning
confidence: 84%